2020
DOI: 10.3390/molecules25092077
|View full text |Cite
|
Sign up to set email alerts
|

New 8-C-p-Hydroxylbenzylflavonol Glycosides from Pumpkin (Cucurbita moschata Duch.) Tendril and Their Osteoclast Differentiation Inhibitory Activities

Abstract: Six new 8-C-p-hydroxybenzylflavonol glycosides were isolated from a hot water extract of pumpkin (Cucurbita moschata Duch.) tendril and elucidated as 8-C-p-hydroxybenzylquercetin 3-O-rutinoside, 8-C-p-hydroxybenzoylquercetin 3-O-β-D-glucopyranoside, 8-C-p-hydroxybenzylkaempferol 3-O-(α-L-rhamnopyranosyl(1→6)-β-D-galactopyranoside, 8-C-p-hydroxybenzoylkaempferol 3-O-rutinoside, 8-C-p-hydroxybenzylisorhamnetin 3-O-rutinoside, and 8-C-p-hydroxybenzylisorhamnetin 3-O-(α-L-rhamnopyranosyl(1→6)-β-D-galactopyranoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The chemical composition and biological properties of different parts of C. moschata have been examined in many investigations confirming that pumpkins have a wide range of bioactivities, such as anti-diabetes, anti-inflammation, hepatoprotective, anticancer, and anti-obesity properties [15][16][17][18][19][20][21][22]. These properties are generally attributedto the content of phenolic acids [23].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition and biological properties of different parts of C. moschata have been examined in many investigations confirming that pumpkins have a wide range of bioactivities, such as anti-diabetes, anti-inflammation, hepatoprotective, anticancer, and anti-obesity properties [15][16][17][18][19][20][21][22]. These properties are generally attributedto the content of phenolic acids [23].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has been collected to show the potential of plant derivatives for the prevention and treatment of bone lesions [ 12 , 13 , 14 ]. Despite various discrepancies in the literature, there is agreement in attributing the positive effects of plant extracts, including those of the pumpkin tendrils, on the bone repair process, to antioxidant and anti-inflammatory action, and to the ability to increase angiogenesis and cell proliferation and differentiation [ 13 , 15 , 16 , 17 ]. Consistently with those observations, the few characteristics of pumpkin leaf extracts known prior to our study suggested that it would be reasonable to investigate their effects on bone cells.…”
Section: Introductionmentioning
confidence: 99%
“…Natural flavonoid compounds are increasingly being recognized for their ability to reduce osteoclast activity and ameliorate critical osteoclastogenesis pathways (Kim et al, 2020 ). Fenugreek's major bioactive component, Orientin, is a C‐glycosyl flavonoid with numerous bioactivities and therapeutic benefits, including anti‐inflammatory, antidiabetes, antioxidative, and autophagy‐inducing properties (Kim et al, 2020 ; Thangaraj et al, 2019 ; Zhang et al, 2022 ). Zhang confirmed that in vitro, Ori could inhibit TBHP‐induced oxidative stress in cells from the rat nucleus pulposus (Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%